A model of externalities for regional manufacturing growth - Mendoza, Eduardo; Martínez, Gerardo (Estudios Económicos de El Colegio de México, 1999)
This paper investigates the impact of externalities on the growth of manufacturing employment in the northern border states of Mexico. The process of economic globalization has been determinant in the restructuring of the manufacturing industry in this region. The study uses a model of externalities, based on relative agglomeration indexes, to develop an econometric assessment of the effect of external economies on manufacturing employment growth. The results show faster growth in the border region, while the central region exhibits a relative decrease.